Associations between voxel-level accumulated dose and rectal toxicity in prostate radiotherapy. (April 2020) - Shelley, Leila E.A.; Sutcliffe, Michael P.F.; Thomas, Simon J.; Noble, David J.; Romanchikova, Marina; Harrison, Karl; Bates, Amy M.; Burnet, Neil G.; Jena, Raj
Highlights: Daily delivered dose calculated and accumulated to rectal wall. Voxel-resolution dose accumulation via finite element modelling. Rectal subregions at risk identified for four toxicity endpoints. Toxicity associations improved using spatial features of accumulated delivered dose. Abstract: Background and Purpose: Associations between dose and rectal toxicity in prostate radiotherapy are generally poorly understood. Evaluating spatial dose distributions to the rectal wall (RW) may lead to improvements in dose-toxicity modelling by incorporating geometric information, masked by dose-volume histograms. Furthermore, predictive power may be strengthened by incorporating the effects of interfraction motion into delivered dose calculations. Here we interrogate 3D dose distributions for patients with and without toxicity to identify rectal subregions at risk (SRR), and compare the discriminatory ability of planned and delivered dose. Material and Methods: Daily delivered dose to the rectum was calculated using image guidance scans, and accumulated at the voxel level using biomechanical finite element modelling. SRRs were statistically determined for rectal bleeding, proctitis, faecal incontinence and stool frequency from a training set (n = 139), and tested on a validation set (n = 47). Results: SRR patterns differed per endpoint. Analysing dose to SRRs improved discriminative ability with respect to the full RW for three of four endpoints. Training set AUC and OR analysis produced stronger toxicity associations from accumulated dose than planned dose. For rectal bleeding in particular, accumulated dose to the SRR (AUC 0.76) improved upon dose-toxicity associations derived from planned dose to the RW (AUC 0.63). However, validation results could not be considered significant. Conclusions: Voxel-level analysis of dose to the RW revealed SRRs associated with rectal toxicity, suggesting non-homogeneous intra-organ radiosensitivity. Incorporating spatial features of accumulated delivered dose improved dose-toxicity associations. This may be an important tool for adaptive radiotherapy in the future.